Migration pressure by refugees: The south-east Bavarian border areas at the end of Balkan Route in 2015-2016 - Jürgen Weber (Cross-border spatial development in Bavaria: Dynamics in cooperation - Potentials of integration, 2022)
In 2015/2016 the Federal Republic of Germany and Bavaria were greatly challenged by the refugee wave from the Middle East, Afghanistan and various African states, and its management. The south-east Bavarian border areas were particularly affected due to their location at the end of the Balkan route. This article first provides an overview of the essential elements of German and Bavarian asylum and refugee policy. It then analyses the special challenges facing the south-east Bavarian border areas before addressing the spatial effects of the refugee wave in these regions. As the task of integration becomes increasingly important, a special opportunity for action-oriented bottom-up regional initiatives can be identified.
urn:nbn:de:0156-41580833; hdl:10419/253270; https://econpapers.repec.org/RePEc:zbw:arlabe:34
Keywords: 710; Refugee wave; asylum and refugee policy in Germany and Bavaria; south-east Bavarian border regions; regional management; bottom-up regional development